Determinant Factors that Impact in the Defection of the University Students - Apaza, Effer (2012)
Through this article I address the issue of dropout students in university education from a conceptual perspective. It discusses the distinctions that are possible to make with respect to this term, in order to adopt fully understand the definitions for future work on factors influencing the college dropout. In addition to having collected a variety of concepts among psychological, economic, sociological, organizational, and interactions between the student and the institution. These factors are predictive for student dropout. Given that more care should be given to some variables that are most critical to decision making in students